Giorgione's ambiguity - Nichols, Tom, 1958- (Renaissance lives., 2020)
"The Venetian painter known as Giorgione or 'big George' died at a young age in the dreadful plague of 1510, possibly having painted no more than thirty works. But many of these are among the most mysterious and alluring in the history of art. Paintings such as the Three Philosophers and The Tempest remain compellingly elusive, seeming to deny the viewer the possibility of interpreting their meaning. Tom Nichols argues that this visual ambiguity was quite deliberate, and that it was essential to Giorgione's approach in all his paintings. Nichols shows that Giorgione abandoned the more intellectual and rationalizing tendencies of Renaissance art, acknowledging the limits to human awareness or understanding. He was also to develop a newly sensual kind of art based on the intimate experiences of the body"--Inside back cover